OpenCL-accelerated first-principles calculations of all-electron quantum perturbations on HPC resources - Wu, Zhikun; Shang, Honghui; Wu, Yangjun; Zhang, Zhongcheng; Liu, Ying; Zhang, Yuyang; Ouyang, Yucheng; Cui, Huimin; Feng, Xiaobing (Frontiers in Chemistry, 2023)
We have proposed, for the first time, an OpenCL implementation for the calculations of all-electron density functional perturbation theory (DFPT) in \aims, enabling all its time-consuming simulation stages, i.e. , the real-space integration of the response density, the Poisson solver for the calculation of the electrostatic potential, as well as the response Hamiltonian matrix to be effectively calculated by utilizing various heterogeneous accelerators. Furthermore, to fully exploit the massively parallel computing capabilities, we have also performed a variety of GPGPU-targeted optimizations, which have significantly improved the execution efficiency by reducing register requirements, branch divergence, and memory transactions. Evaluations on the Sugon supercomputer have shown that, notable speedups could be achieved across various materials.